Motilità e criopreservazione di spermatozoi di organismi marini: applicazioni biotecnologiche in acquacoltura ed ambiente - Silvestri, Fausto (2013)
In most aquatic organisms, especially those that have external fertilization, sperm motility is a fundamental parameter for the success of fertilization. In fact the knowledge of sperm motility can be very useful in the aquaculture and ecotoxicological sectors improving breeding procedures, cryopreservation protocols and spermiotoxicity assays. In this sense, this study aimed to: (1) obtain the basic knowledge on sperm motility of aquaculture marine organisms; (2) propose and optimize protocols for sperm cryopreservation; (3) propose and optimize ecotoxicological tests using cryopreservated sperm. For this we used the Mediterranean native organisms Mytilus galloprovincialis, Tapes decussatus, Paracentrotus lividus and Sparus aurata, the alien molluscs cultured in Italy Crassostrea gigas and Tapes philippinarum and the Brazilian native molluscs Perna perna, Crassostrea brasiliana, Crassostrea rhizophorae and Nodipecten nodosus. N. nodosus, M. galloprovincialis and T. decussatus showed the best performance in the general evaluation of physiological parameters of sperm motility. In general the method of sperm acquisition affected the performance of sperm motility of the studied species. For some species, the stored sperm at low temperatures for a short period has proved viable after activation. The N. nodosus sperm showed good viability to cryopreservation through the addition of EG 7% for 10 minutes of adaptation at room temperature and freezing gradient of -6°C/min. A reduced sperm motility was observed after cryopreservation and thawing of P. lividus, P. perna and C. brasiliana. The ecotoxicological assay through S. Aurata cryopreserved sperm demonstrated a remarkable potential as an universal test in the evaluation of different aquatic ecosystems. The species M. galloprovincialis, T. decussatus and N. nodosus were considered as potentially useful with biological systems in spermiotoxicity tests.